Fmp30, Mdm31, and Mdm32 Function in Ups1-Independent Cardiolipin Accumulation Under Low Phosphatidylethanolamine Conditions. (March 2018) - Miyata, Non; Kuge, Osamu
Maintenance of the cardiolipin (CL) level largely depends on Ups1-Mdm35 complex-mediated intramitochondrial phosphatidic acid transfer. In addition, the presence of an alternative CL accumulation pathway has been suggested in the yeast Saccharomyces cerevisiae . This pathway is independent of the Ups1-Mdm35 complex and stimulated by loss of Ups2, which forms a complex with Mdm35 and mediates intramitochondrial transfer of phosphatidylserine for phosphatidylethanolamine synthesis. Recently, we found that the alternative CL accumulation pathway is enhanced by a lowered phosphatidylethanolamine level, not by loss of Ups2 per se, and depends on three mitochondrial inner membrane proteins, Fmp30, Mdm31, and Mdm32.